In Silico and In Vitro Analysis of the 4, 4′, 4′′-((1, 3, 5-Triazine-2, 4, 6-triyl)tris(azanediyl))triphenol), an Antioxidant Agent with a Possible Anti-Inflammatory Function. (22nd May 2019) - Castro, Ricardo I.; Valenzuela-Riffo, Felipe; Morales-Quintana, Luis
Abstract : Inflammation is a consequence of an array of biological reactions that occur in response to pain sensation, local injury, and cell damage. A large number of studies have demonstrated that quercetin and other flavonoids show anti-inflammatory effects; thus, in the present work, we evaluated a triazine-phenol derivative (TP derivative) compound as a possible drug candidate with anti-inflammatory activity. This compound was studied as a possible anti-inflammatory drug using synthesis and characterization by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and mass spectrometry (MS). The derivative of melamine was evaluated for its antioxidant activity and exhibited good DPPH and FRAP antioxidant activity. Additionally, we evaluated the putative effect of the molecule on the COX-2 enzyme through molecular dynamic simulation (MDS), and the result suggested that the TP derivative is a potential anti-inflammatory agent that can interact with the COX-2 enzyme because of the high number of protein-ligand interactions observed with MDS. Finally, the study of theoretical physicochemical properties, the observation of low toxicity (hemolysis assay), and the evaluation of oral bioavailability of the TP derivative showed that it is a possible anti-inflammatory drug candidate.